2015
DOI: 10.1016/j.ophtha.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Ocular Myasthenia Gravis

Abstract: Conversion rates from ocular to generalized myasthenia gravis may be lower than previously reported both in immunosuppressed and nonimmunosuppressed patients. A subset of patients may continue to convert to generalized disease beyond 2 years from onset of symptoms, and close monitoring should be continued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 16 publications
4
38
1
Order By: Relevance
“…Contrast to 90% of conversion rate without immunosuppressive treatments, only 38 patients (17.0%) of 223 OMG patients under sufficient immunosuppressive treatments converted to GMG in the present study. This result was consistent with previous studies which compared the conversion rate of the immunosuppressed group and the non-immunosuppressed group [6,7,13,14]. Yet the predictors for these patients who received early immunosuppressive therapy still remain unknown.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Contrast to 90% of conversion rate without immunosuppressive treatments, only 38 patients (17.0%) of 223 OMG patients under sufficient immunosuppressive treatments converted to GMG in the present study. This result was consistent with previous studies which compared the conversion rate of the immunosuppressed group and the non-immunosuppressed group [6,7,13,14]. Yet the predictors for these patients who received early immunosuppressive therapy still remain unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Reports deemed that OMG patients have lower conversion rates with longer disease duration [13,24,26]. In our study, disease duration came out of multivariate logistic regression analysis as the predictors of GMG conversion.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have reported rates of generalization between 7-36% in the paediatric population [7]. However, in the study conducted by Nagia et al, a much lower overall conversion rate of 21% was reported [8].…”
Section: Ocular Manifestationsmentioning
confidence: 88%
“…However, these patients should not be assured that the risk of conversion after 2 years is minimal, since previous reports showed that 30% of patients convert beyond two years and therefore should continue to be monitored in the long-term [8].…”
Section: Ocular Manifestationsmentioning
confidence: 99%